Investigation of electric and magnetic characteristics of high-temperature hall sensor based on AlGaN/GaN heterostructure - Stempitsky, V. R.; Dao, Dinh Ha (Technology and design in electronic equipment, 2017)
The paper presents research results on the characteristics of Hall sensor based on the AlGaN/GaN heterostructure with various geometric parameters of the active region operating in the temperature range from –25 to 400ºC. The research was performed using device-technological simulation. The active layer of the proposed structure is a two-dimensional electron gas region, which is formed between the barrier layer Al0,3Ga0,7N and the undoped GaN channel layer. The results (room temperature current-related magnetic sensitivity 66.4 V/(A·T) and very low temperature cross sensitivity of 0,0273%/ºC) indicate the prospects of the proposed solutions for the practical use.